Pengaruh Kualitas Produk Skincare Fenny Frans terhadap Kepuasan Pelanggan di Kota Palopo - Keshi Mutih Palma; Hapid Hapid; Altri Wahida (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Product quality is a combination of features and characteristics. Determine how well the output can meet customer requirements, or evaluate how well the characteristics and properties meet their requirements. Product quality or quality is the main aspect that can attract customers. Customer satisfaction is a person's feeling of pleasure or disappointment that occurs when the performance (or results) of a product are compared to expected performance. The purpose of this study was to determine the effect of product quality on customer satisfaction in the city of Palopo. This research was carried out in the city of Palopo. This type of research uses quantitative research with a sample of 30 respondents, while the method used in this research is a questionnaire survey. Questionnaires are used as a data collection tool, the data used in this study uses primary data. Analysis of the data used to test the validity, reliability, partial test. The results of this study indicate that the product quality variable has a positive value on the customer satisfaction variable. It can be said that the higher the perception of customer satisfaction, the higher the level of product quality received by customers. Keywords: Product Quality; Customer Satisfaction